Simulation Study Using SIMULINK/MATLAB on THD for PV Grid Connected System - Suliana, Abd Ghani; Lafsah, Mat Daud; Noor Zirwatul Ahlam, Naharuddin (2012)
Total harmonic distortion (THD) is a measurement of the harmonic distortion and is defined as the ratio of the sum of the powers of all harmonic components to the power of the fundamental frequency. The purpose of this paper is simulation study on THD for photovoltaic (PV) grid connected. A scale-down less than 1kW system will be developed and established for the study. The impact on THD will be assessed to simulate the real network environment by varied motor loads and the utility grid also will be measured. The motor is connected to Adjustable speed Drives (ASDs) as the load. The simulation is done by using MATLAB/Simulink software and the simulation results will be collected and analyzed.